Verificação formal aplicada à análise de confiabilidade de sistemas hidráulicos - Bozz, Claudia Beatriz (2018)
Real time systems that have continuous behavior associated with discrete elements are called hybrid systems. Among them, in this master’s research, a hydraulic system has been chosen as an object of study in order to perform the reliability analysis of it through modeling and formal verification. Much as several models for the reliability analysis of complex systems have been proposed in the literature, most of them are not suitable to represent the system when its behavior needs to be expressed by means of continuous variables, like the case of hybrid systems. Generally, simulation and experimental testing are used to analyze systems, and they give only approximate results from a large amount of samples. To eliminate the limitations of these techniques, the formal verification is an effective alternative, since it is characterized by performing a sweep in all possible states of the system automatically, verifying the behavior as a whole. The UPPAAL STRATEGO toolkit for modelling by stochastic hybrid automata and model checking has been used in this work, both classic formal verification and statistical formal verification. A benckmark has been used as object of study. Initially, the system has been modelling and its behavior (physical and controlled) verified through simulation and formal verification (property specification and model checking). The reliability parameters obtained in the statistical analysis of the system failures have been compared with results of literature, presenting a dispersion less than 2.5%, so it can be verify that the methodology used and the models constructed were adequate to analyze the reliability of this system hybrid.In a second step of this work, the probability distribution of failure of the components have been modified, in order to become the system more reliable with real hydraulic systems, and estimate the optimum mean time between maintenance (MTBM) of this system. Thus, it’s possible to conclude that the methodology is adequate to perform the reliability analysis of the hydraulic system, being that model checking is effective to estimate the reliability parameters of the hydraulic system.